BASS ten years on: A personal reflection. Issue 1 (2nd January 2020) - Swinton, John
ABSTRACT: This article revisits the speech made by John Swinton at the inauguration of the British Association for the Study of Spirituality (BASS) in January 2010. It argues that some of the difficulties in defining spirituality can be clarified and addressed if we think of spirituality not simply in definitional terms, but in relation to how we use it in practice. It provides a critique of the ways in which ideas about spirituality are constructed, and offers some thoughts as to how we might move away from the search for definitions towards a focus on the impact that spirituality has on the humanness of our practices, including its peace-making potential within fragmented societies.